2022
DOI: 10.3390/brainsci12111525
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Sleep and Mental Health on Working Memory and Academic Performance: A Longitudinal Study

Abstract: Sleep and mental health can affect cognition and academic performance. The present study aimed to investigate the relationships between sleep, mental health, working memory, and academic performance. We collected demographic data from university students during the non-academic summer period and the academic term. We also measured academic performance (GPA), sleep (PSQI), depression (PHQ-9), anxiety (GAD-7), and disordered social media use (SMDS). Working memory was assessed by the Cambridge Neuropsychological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 60 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…For instance, Smith et al (2023) conducted a study with 302 adolescent participants and found that teenagers with attention deficit or hyperactivity disorders generally exhibit lower levels of learning motivation, which in turn affects their academic performance. The internal factors such as sleep (Boraita et al, 2023;Chan et al, 2023;Hamvai et al, 2023), depression (Song et al, 2023;Urbanska-Grosz et al, 2023), and disordered social media use (Almarzouki et al, 2022;Sserunkuuma et al, 2023) also exert varying degrees of influence on academic performance. In this study, we primarily investigate the internal factors pertaining to learning state, encompassing self-efficacy and learning behavior.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Smith et al (2023) conducted a study with 302 adolescent participants and found that teenagers with attention deficit or hyperactivity disorders generally exhibit lower levels of learning motivation, which in turn affects their academic performance. The internal factors such as sleep (Boraita et al, 2023;Chan et al, 2023;Hamvai et al, 2023), depression (Song et al, 2023;Urbanska-Grosz et al, 2023), and disordered social media use (Almarzouki et al, 2022;Sserunkuuma et al, 2023) also exert varying degrees of influence on academic performance. In this study, we primarily investigate the internal factors pertaining to learning state, encompassing self-efficacy and learning behavior.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Smith et al (2023) conducted a study with 302 adolescent participants and found that teenagers with attention deficit or hyperactivity disorders generally exhibit lower levels of learning motivation, which in turn affects their academic performance. The internal factors such as sleep (Boraita et al, 2023;Hamvai et al, 2023), depression (Song et al, 2023;Urbanska-Grosz et al, 2023), and disordered social media use (Almarzouki et al, 2022;Sserunkuuma et al, 2023) also exert varying degrees of influence on academic performance. In this study, we primarily investigate the internal factors pertaining to learning state, encompassing self-efficacy and learning behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Academic years can be exceedingly demanding for students. A significant number of students struggle with effectively managing their academic obligations and coordinating their study-life balance, while also expressing apprehension about securing a profession in a highly competitive job market [ 4 ]. Consequently, this particular demographic is vulnerable to developing mental health problems during their time in university [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Working memory is a type of memory that maintains knowledge that is important for the current task while the brain performs other mental processes. It is a crucial cognitive function in the process of learning [ 4 ].…”
Section: Introductionmentioning
confidence: 99%